Hometown Transnationalism and the Emergence of Indonesian Diaspora Organizations in Europe - Meilinda Sari Yayusman; Ayu Nova Lissandhi (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2022)
This article aims to explain the movement of Indonesian diaspora and their initiative to create multifarious new activities in today’s globalized era. Focusing on Indonesian diaspora organizations in Europe, namely Indonesian Diaspora Networks (IDN) in the Netherlands and France who are eager to come together, build organizations based on a common identity, and contribute to Indonesia. The newly-emerged concept of hometown transnationalism is used to explain the phenomenon in which collective remittances through development projects are the main output of diasporas’ contribution. Qualitative method is applied to this study through a set of in-depth interviews, a study of life history, and literature review completed by site visits to observe diasporas’ works. The results of this study show that the emergence of various diaspora organizations is the impact of the increasingly rapid movement of people and technological developments, thus encouraging the diaspora to be more connected to their hometowns. Both IDNs play a vital role in realizing diaspora's aspirations to develop Indonesia through multifarious ways. Keywords: diaspora organizations, hometown transnationalism, Indonesian diaspora, Indonesian diaspora networks